2020
DOI: 10.1002/ajim.23090
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐quantitative job exposure matrix for dust exposures in Swedish soft tissue paper mills

Abstract: Background Total paper dust exposure has been associated with respiratory problems among workers in the soft tissue paper industry. However, a comprehensive job exposure matrix (JEM) has not been developed for application to this industry. Our study was intended to address this need and to support further studies of mortality and morbidity in a cohort of Swedish workers from this industry. Methods We evaluated four participating soft tissue paper mills in Sweden. We combined information on process and equipmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The exposure assessment of soft paper dust was based on a validated job-exposure matrix. 17 Data on cancer outcomes were based on the Swedish Cancer Registry, which are considered to have high quality. 29 An important strength was the prospective design with cohort inclusion based on personnel files from the mills which resulted in a cohort of nearly all workers employed in these mills during the study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exposure assessment of soft paper dust was based on a validated job-exposure matrix. 17 Data on cancer outcomes were based on the Swedish Cancer Registry, which are considered to have high quality. 29 An important strength was the prospective design with cohort inclusion based on personnel files from the mills which resulted in a cohort of nearly all workers employed in these mills during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…In all mills area and personal sampling of total dust was conducted starting in the early 1970s as previously described. 15,17 We have T A B L E 1 Descriptive data of the included workers from three Swedish soft paper mills. previously shown that total dust in soft paper mills can be used as a proxy for soft paper dust.…”
Section: Exposure Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…O mecanismo responsável por essa associação pode estar relacionado ao fato de substâncias químicas, potencialmente ototóxicas, estarem presentes nas partículas de poeira. A poeira tem sido citada como meio de contaminação com outras substâncias químicas, tais como os pesticidas e o pó de chumbo 7 ; bem como causadora de problemas respiratórios 49,50,51,52,53,54 , os quais podem ter influência no sistema auditivo 55,56 . Além disso, em muitos ambientes de trabalho nos quais a poeira está presente, como construção civil 9 e marmorarias 57 , em geral, os níveis de ruído também são elevados.…”
Section: Discussionunclassified
“…The exposure assessments have been described in more detail in a recent publication. 13 Due to variations in exposure across time and duties, most workers were classified into more than one exposure category over the study period. The exposure assessments are presented in table 3 .…”
Section: Methodsmentioning
confidence: 99%